Beyond survival in solid organ transplantation: a summary of expert presentations from the Sandoz 6th Standalone Transplantation Meeting, 2018 - Legendre, Christophe; Viebahn, Richard; Crespo, Marta; Dor, Frank; Gustafsson, Bengt; Samuel, Undine; Karam, Vincent; Binet, Isabelle; Aberg, Fredrik; Geest, Sabina de; Moes, Dirk Jan A. R.; Tönshoff, Burkhard; et al. (Transplantation, 2019)
An abstract is unavailable.